ANALYSING STRATEGY USE IN TERMS OF THE FOUR PARAMETERS OF STRATEGIC COMPETENCE: CONTRIBUTIONS FROM A NUMEROSITY JUDGEMENT TASK - Luwel, Koen; Verschaffel, Lieven (Anales de Psicología / Annals of Psychology, 2008)
The present paper discusses three studies that all relied on Le-maire and Siegler’s (1995) theoretical framework for analyzing people’s strategy use in the context of a numerosity judgment task. This framework distinguishes between four different parameters of strategic competence: repertoire, frequency, efficiency and adaptivity. In Study 1, we applied this framework for studying developmental changes in children’s numerosity judgment strategies. In Study 2, we analysed the contribution of intelligence on these four parameters and assessed the extent to which the provision of feedback could lead to an improvement in one or more of these parameters. In Study 3, we investigated whether variations in the task context would lead to alterations in one or several of these parameters. At the end of the paper, we reflect on the broader applicability of this theoretical framework and the research findings that it has yielded.